Strategy and Online Business Development as Effort to Increase Productivity and Income - Manik, Fuzy Yustika; Br Ginting, Dewi Sartika; Yuliaty, Tetyy (Talenta Publisher, 2023)
Rambung Barat Village has several Village Community Institutions, one of which is the Family Welfare Development (PKK) group. In carrying out its work program, PKK administrators are faced with obstacles on how to make the community able to make their families prosperous by improving the family's economy. Having a large number of households becomes a new threat and problem for the village. How the Lurah and PKK administrators are able to encourage every household to become a prosperous family. Through PKK, women have been invited to be able to produce and process products that are of sale value. So this PKK group has the potential to be able to help the family economy during this pandemic by starting and developing businesses. However, there are still obstacles, the pandemic has forced people in general to change from their old habits. The people's purchasing power has decreased as well as the government's recommendation to maintain physical distancing and stay at home. So we need a solution to still be able to market the products that have been produced by utilizing technology. Currently, every individual must be prepared to face a cultural shift where every fulfillment of needs must go hand in hand with technological developments. So it will be important for the PKK group to increase knowledge about the use of technology in developing businesses such as knowledge in building online stores as one of the sales strategies carried out. With this service activity, the PKK group has additional knowledge that can be used to develop its business. So that in the end it can help the family economy in particular and improve the economy of a country that is still hit by the COVID-19 pandemic